Common features of the Czechoslovak political trials of the 1950s and in Arthur Miller´s The Crucible - Chmelíková, Linda (Univerzita Pardubice, 2011)
The aim of this paper is to analyze common features of Czechoslovak political trials and witch trials in Arthur Miller´s The Crucible. It provides a description of both political and witch trials. Furthermore, it focuses on the period of time when the play The Crucible was written.
Společné rysy politických procesů 50. let 20. století v Československu a v Arthur Millerově "Zkouška ohněm"
Keywords: hon na čarodějnice; politické procesy; McCarthismus; Zkouška ohněm; witch hunts; McCarthyism; political trials; The Crucible; Miller, Arthur